Communicating evidence about the environment's role in obesity and support for government policies to tackle obesity: a systematic review with meta-analysis. Issue 1 (2nd January 2022) - Reynolds, James P.; Vasiljevic, Milica; Pilling, Mark; Marteau, Theresa M.
ABSTRACT: Public support for many policies that tackle obesity by changing environments is low. This may reflect commonly held causal beliefs about obesity, namely that it is due to failures of self-control rather than environmental influences. Several studies have sought to increase public support by changing these and similar causal beliefs, with mixed results. The current review is the first systematic synthesis of these studies. Searches of PsycInfo, Medline, Web of Science, Scopus, and Open Grey yielded 20 eligible studies ( N = 8977) from 11, 776 abstracts. Eligible studies were controlled experiments with an intervention group that communicated information about the environment's role in obesity, and a measure of support for environment-based obesity policies. The protocol was prospectively registered on PROSPERO. Meta-analyses showed no evidence that communicating information about the environment's influence on obesity changed policy support or the belief that the environment influences obesity. A likely explanation for this null effect is the ineffectiveness of interventions that were designed to change the belief that the environment influences obesity. The possibility remains, however, that the association observed between beliefs about the causes of obesity and attitudes towards obesity policies is correlational and not causal.